2021
DOI: 10.3934/eect.2020063
|View full text |Cite
|
Sign up to set email alerts
|

Periodic solutions and multiharmonic expansions for the Westervelt equation

Abstract: In this paper we consider nonlinear time periodic sound propagation according to the Westervelt equation, which is a classical model of nonlinear acoustics and a second order quasilinear strongly damped wave equation exhibiting potential degeneracy. We prove existence, uniqueness and regularity of solutions with time periodic forcing and time periodic initial-end conditions, on a bounded domain with absorbing boundary conditions. In order to mathematically recover the physical phenomenon of higher harmonics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…. Thus we have shown that T is a self-mapping, provided (23), (25), (28), (29), (30) hold. These can be achieved by making κ L ∞ (Ω) small:…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…. Thus we have shown that T is a self-mapping, provided (23), (25), (28), (29), (30) hold. These can be achieved by making κ L ∞ (Ω) small:…”
mentioning
confidence: 71%
“…We now proceed to derive contractivity of T by applying the estimates (20), (21) to the pde (19). In the above, we have already shown that for any p ∈ M , under conditions (23), (25), (28), (29), (30), the coefficients α = 1 − 2κp t , β ≡ b, γ ≡ c 2 , δ ≡ 0, µ ≡ 0 satisfy the assumptions of Lemma 2.1 with 1 2 ≤ α ≤ 3 2 ,γ ≤γ < 1 16 , so that the estimates (20), (21) with u(0) = 0, u t (0) = 0 apply to (19). Using them together with Gronwall's inequality yields existence of constants C,C > 0 (depending only on the constants R 0 , R 1 , R 2 ,γ in the definition of M as well as b, c 2 and T ), such that…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…To achieve the separability (33) of m we supplement the boundary excitation ĝk (𝜔) by an interior one f g k ( ) , which we view as an approximation of a source g(𝜔) 𝛿 Σ k concentrated on Σ k , cf., e.g., [15]. The resulting equation for φk (𝜔) then has a solution of the form φk (x, 𝜔) = ã(𝜔) b(x) if, e.g., we choose b such that…”
Section: Uniquenessmentioning
confidence: 99%